Vinasse as a substrate for inoculant culture and soil fertigation: Advancing the circular and green economy - Torres, Mariela Analía (2023)
Vinasse is a by-product with a key role in circular economy. In this work, we analyze sugarcane vinasse as culture medium for obtaining single and mixed inoculants. Trichoderma harzianum MT2 was cultured in single and sequential co-culture with Pseudomonas capeferrum WCS358 or Rhizobium sp. N21.2. Fungal biomass in single culture was more than three folds higher in vinasse than in a standard medium, and was higher in co-culture with Rhizobium sp. N21.2 than with P. capeferrum WCS358. Bacterial growths in vinasse, in particular P. capeferrum WCS358, were improved in co-culture with T. harzianum MT2. Residual vinasses, obtained after microbial growth, presented almost neutral pH and lower conductivities and toxicity than raw vinasse. Fertigation with residual vinasses modifies characteristics of soil evidenced in the total N, cation exchange capacity, urease and acid phosphatase, and microbial metabolic diversity, in comparison to raw vinasse. In general, soil fertigation with residual vinasse from co-culture with P. capeferrum WCS358 is more similar to irrigation with water. Treatment evaluation indicates that vinasse is suitable for the production of mixed inoculants containing T. harzianum. The co-culture with P. capeferrum WCS358 improves the characteristics of the residual vinasse allowing a fertigation with less detrimental effect in soil in comparison to Rhizobium sp. N21.2. Obtaining valuable biomass of single or mixed inoculants in vinasse with lower ecological impact is relevant for the circular and green economy.